Lack of correlation between central sensitization inventory and psychophysical measures of central sensitization in individuals with painful temporomandibular disorder - Proença, Juliana dos Santos [UNESP]; Baad-Hansen, Lene; Braido, Guilherme Vinícius do Vale [UNESP]; Mercante, Fernanda Gruninger [UNESP]; Campi, Letícia Bueno [UNESP]; Gonçalves, Daniela Aparecida de Godoi [UNESP] (Elsevier, 2021)
Objective: To assess the correlation between the Central Sensitization Inventory (CSI) scores and the results of psychophysical tests and psychosocial questionnaires according to the presence of painful temporomandibular disorder (TMD). Design: It was a cross-sectional study involving 146 participants, aged 20–65 years. Painful TMD was classified using the Research Diagnostic Criteria for Temporomandibular Disorders. CSI was applied to assess “central sensitization-related symptoms”, as has been suggested. Wind-up ratio, pressure pain threshold and conditioned pain modulation were used as psychophysical tests to evaluate signs and symptoms of central sensitization. Psychosocial factors were assessed by the presence of non-specific physical symptoms, depressive and anxiety symptoms. The sample was divided into two groups: Control (n = 31); Painful TMD (n = 115). Descriptive statistics characterized the sample. Correlation analysis were performed using Pearson's and Spearman's correlation coefficients (α = 5%). Results: Of the total sample, 78.8 % presented painful TMD, and the mean (standard deviation) age was 37.4 (±11.5) years. Anxiety symptoms (p = 0.028) and non-specific physical symptoms (p < 0.001) were more frequent in the painful TMD group than in controls. Painful TMD patients presented higher scores of the CSI (p < 0.001) and lower pressure pain thresholds (p ≤ 0.020) compared to controls. CSI scores were significantly correlated with psychosocial measures (p < 0.001) but not with psychophysical tests (p ≥ 0.089). Conclusion: The CSI scores did not correlate with psychophysical measures of central sensitization but were positively correlated with the results of psychosocial questionnaires.
Keywords: Central nervous system sensitization; Pain measurement; Pain threshold; Questionnaires; Temporomandibular joint disorders